The influence of aerobic power on repeated anaerobic exercise in junior soccer players - Cipryan, L.; Gajda, V. (Journal of Human Kinetics, 2011)
The main purpose of the present study is to investigate the relationship between anaerobic power achieved in repeated anaerobic exercise and aerobic power. The study group consisted of 40 soccer players (age 17.3 +/-1.36 years). All participants performed 3 tests: a running-based anaerobic sprint test (RAST), a graded treadmill test (GXT), and a multistage fitness test (20mPST). A statistically significant correlation was found among peak power in the GXT and the maximum (r = 0.365, p=0.02), minimum (r=0.334, p=0.035) and average (r=0.401, p=0.01) power in the RAST. No relationships were found between VO2max obtained from both aerobic tests and any performance indices in the RAST. A statistically significant correlation was found between the VO2max obtained from the spiroergometry examination (GXT) and the calculated VO2max of 20mPST (r=0.382, p=0.015). In conclusion, the level of VO2max does not influence the performance indices in the RAST in elite junior soccer players. It is possible that the modification of anaerobic test protocol or a more heterogeneous study group would influence the results. The estimation of the VO2max in the 20mPST is too inaccurate and should not replace the laboratory spiroergometry examination.